Analisis Risiko Usahatani Wortel Di Kelurahan Rurukan Kecamatan Tomohon Timur Kota Tomohon - Beslar, Chris Wilson; Waney, Nordy Fritsgerald Lucky; Manginsela, Elsje Pauline (Sam Ratulangi University, 2024)
The purpose of the study was to analyze the priority risks in carrot farming in Rurukan Village, East Tomohon District, Tomohon City. This research was conducted for four months from October 2023 to January 2024, located in Rurukan Village, East Tomohon District, Tomohon City. The data collection method used in this study was the survey method. Data were obtained from direct interviews with carrot farmers, by asking questions in the form of a prepared questionnaire. Supported by data obtained from the Tomohon City Agriculture Office, Tomohon City Central Bureau of Statistics, and Rurukan Village Office. The sampling method used is purposive sampling method to farmers who grow carrots until the last planting season in 2023. The sample in this study were carrot farmers in Rurukan Village with a total of 10 respondents (farmers). The analysis used in this research is descriptive qualitative analysis. The data obtained were identified and then processed with FMEA (Failure Mode and Effect Analysis) analysis tools to assess the risks that could potentially arise. The results showed that the risk analysis of carrot farming in Rurukan Village, East Tomohon Subdistrict, Tomohon City showed that there were four potential failures that became risk priorities, namely the long dry season, pest attacks, high rainfall, price fluctuations. The results of the assessment based on FMEA (Failure Mode and Effect Analysis) analysis show that farmers are not maximizing their efforts in handling the risks that occur in carrot farming.